2020
DOI: 10.1002/9781119127383.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Dependence of the Streaming Potential Coefficient

Abstract: Observations of streaming potential for unsaturated conditions do not always show the same trend depending on the hydrodynamic conditions and because of a lake of coherency between the data processing procedures. We combine the data from three studies published in the literature, acquired during non-steady state drainage experiments, and apply the same processing steps. We model the hydrodynamic behaviour of these experiments to confirm that they experienced different flow dynamics. We argue that the raw SP da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 163 publications
(215 reference statements)
2
1
0
Order By: Relevance
“…In the last of these references, as it was previously suggested by Allègre et al (2014); Allégre et al (2015), it was shown through a numerical lattice-Boltzmann procedure that indeed the polarization of the air-water interface does play an important role both in the amplitude of the electrokinetic coupling and in its non monotonic behavior. These results were reaffirmed by the analysis performed by Jouniaux et al (2020) revisiting laboratory data published by different authors.…”
Section: Introductionsupporting
confidence: 66%
“…In the last of these references, as it was previously suggested by Allègre et al (2014); Allégre et al (2015), it was shown through a numerical lattice-Boltzmann procedure that indeed the polarization of the air-water interface does play an important role both in the amplitude of the electrokinetic coupling and in its non monotonic behavior. These results were reaffirmed by the analysis performed by Jouniaux et al (2020) revisiting laboratory data published by different authors.…”
Section: Introductionsupporting
confidence: 66%
“…These results were reaffirmed by the analysis performed by Jouniaux et al (2020) revisiting laboratory data published by different authors.…”
Section: Introductionsupporting
confidence: 66%
“…Moreover, the signature is affected by the subsurface hydraulic and electrical properties (Hu et al, 2020). Thus, when combined with hydrological and biogeochemical processes, the SP technique can be specifically used to localize and quantify water flow (e.g., pumping test and water leakage) (Oliveti and Cardarelli, 2017) and redox-sensitive contaminant distribution (e.g., metallic and organic matter) (Revil et al, 2009;Forté and Bentley, 2013) and estimate soil hydraulic and electrical properties (e.g., hydraulic and electrical conductivity) (Jouniaux et al, 2020).…”
Section: Introductionmentioning
confidence: 99%